Assessment of Auricularia cornea var. Li. polysaccharides potential to improve hepatic, antioxidation and intestinal microecology in rats with non-alcoholic fatty liver disease - Zhou, Tiantian; Mao, Xue; Jiang, Wei; Pan, Yu; Chen, Xijun; Hu, Jihua; Kong, Xianghui; Xia, Haihua (Frontiers in Nutrition, 2023)
Non-alcoholic fatty acid liver disease (NAFLD) is a reputed global health con-cern, affecting children and young adults. Accumulating evidence suggests that edible fungi polysaccharides have the potential to relieve NAFLD. Our previous study found that Auricularia cornea var. Li. polysaccharides (ACP) could improve immune by regulating gut microbiota. However, its NAFLD-alleviating potentials have been scarcely reported. This study analyzed the protective effects of Auricularia cornea var. Li. polysaccharides on HFD-induced NAFLD and mechanistic actions. We first ana-lyzed the histology and hepatic lipid profile of animals to evaluate this variant’s ameliorating effects on NAFLD. Then, antioxidant and anti-inflammatory potentials of ACP were studied. Finally, we explored changes in the gut microbiome diversity for mechanistic insights from the gut-liver region. Results showed that supplementation with ACP substantially reduced homeostasis model assessment (HOMA-IR), body fat, liver index rates and weight gain (p < 0.05). This variant also improved HDL-C levels while decreasing triglyceride (TG), total cholesterol (TC), and low-density lipopro-tein cholesterol (LDL-C) levels which were initially triggered by HFD. ACP media-tion also decreased the serum alanine aminotransferase (ALT) and aspartate ami-notransferase (AST) levels considerably with H&E technique indicating that it can reduce liver lipid accumulation, thus lowering liver damages risks (p < 0.05). The antioxidant potentials of ACP were also demonstrated as it decreased the hepatic levels of malondialdehyde (MDA) and increased the activities of superoxide dis-mutase (SOD), catalase (CAT), and glutathione peroxidase (GSH-PX). Proinflam-matory markers like IL-6, IL-1β and TNF-α concentrations were decreased by ACP supplementation, accompanied with increased IL-4 levels. Finally, this variant re-versed deleterious patterns triggered by HFD induction back to levels similar with the control group. In all, ACP protects HFD-induced NAFLD by improving liver charac-teristics and regulating colonic flora composition, our findings assert that ACP can be a promising strategy in NAFLD therapy.